Social-Ecological Institutional Fit in Volunteer-Based Organizations: A Study of Lake Management Organizations in Vilas County, Wisconsin, U.S.A. Issue 1 (11th June 2021) - Whittaker, Dane; Crippen, Alise; Johnson, Corinne; Janssen, Marco A.
How do the social and ecological attributes of social-ecological systems enable outcomes of those systems? The high concentration of lake organizations in northern USA enables us to study social, institutional, and ecological attributes that correlate with performance of common pool resource governance—institutional fit. In the summer of 2019, we performed an in-depth comparative study of thirty-one lake organizations in Vilas County, Wisconsin using data collected through semi-structured interviews, websites, and agency databases. We systematically compared the cases using crisp-set qualitative comparative analysis, specifically analyzing how the eight Ostrom institutional design principles lead to different outcomes for the lake social-ecological systems. The Ostrom institutional design principles played an important role in SES governance outcomes where there was low-resource dependence. We found that different combinations of design principles, social, and ecological conditions led to the same lake SES outcomes—equifinality. Although we expected that there were no panaceas for lake governance, we were surprised by the high diversity in organizational goals and the relative low diversity of rules in use.